1998
DOI: 10.1172/jci1554
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate and sulfasalazine promote adenosine release by a mechanism that requires ecto-5'-nucleotidase-mediated conversion of adenine nucleotides.

Abstract: We and others have shown that an increased extracellular concentration of adenosine mediates the antiinflammatory effects of methotrexate and sulfasalazine both in vitro and in vivo, but the mechanism by which these drugs increase extracellular adenosine remains unclear. The results of the experiments reported here provide three distinct lines of evidence that adenosine results from the ecto-5'-nucleotidase- mediated conversion of adenine nucleotides to adenosine. First, pretreatment of a human microvascular e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
162
1
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(173 citation statements)
references
References 22 publications
6
162
1
4
Order By: Relevance
“…CD73 modulates the extent of immune and inflammatory responses in vitro and in vivo. These effects are mediated via its enzymatic capability to hydrolyse adenosine monophosphate 5 0 -AMP into adenosine, an immunomodulatory purine compound [16][17][18].We have recently shown that CD73 is upregulated on vascular endothelium in a time-and dose-dependent manner after treatment with type-I IFN-a in vitro and in vivo [19], but how IFN-b affects CD73 in brain EC and in the context of MS has never been studied before. As adenosine, the end product of the CD73 catalytic reaction, has both anti-inflammatory and neuroprotective effects, we hypothesized that IFN-b might also exert some of its beneficial effects on MS-disease pathology by regulating CD73-mediated adenosine production.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CD73 modulates the extent of immune and inflammatory responses in vitro and in vivo. These effects are mediated via its enzymatic capability to hydrolyse adenosine monophosphate 5 0 -AMP into adenosine, an immunomodulatory purine compound [16][17][18].We have recently shown that CD73 is upregulated on vascular endothelium in a time-and dose-dependent manner after treatment with type-I IFN-a in vitro and in vivo [19], but how IFN-b affects CD73 in brain EC and in the context of MS has never been studied before. As adenosine, the end product of the CD73 catalytic reaction, has both anti-inflammatory and neuroprotective effects, we hypothesized that IFN-b might also exert some of its beneficial effects on MS-disease pathology by regulating CD73-mediated adenosine production.…”
mentioning
confidence: 99%
“…CD73 modulates the extent of immune and inflammatory responses in vitro and in vivo. These effects are mediated via its enzymatic capability to hydrolyse adenosine monophosphate 5 0 -AMP into adenosine, an immunomodulatory purine compound [16][17][18].…”
mentioning
confidence: 99%
“…This enzyme modulates cartilage homeostasis and displays increased levels of activity in diseased cartilage [99,100]. Chondrocytes in osteoarthritic lesions show elevated 5NT activity relative to nonlesioned areas, and this causes increased extracellular adenosine levels, and in turn, higher intracellular concentrations via transporters.…”
Section: P1 Receptors: A2armentioning
confidence: 99%
“…Trabalhos também propõem que a eficácia terapêutica observada com a administração de baixas doses de MTX, é decorrente de sua capacidade em manter e aumentar os níveis de adenosina extracelular (Cronstein et al, 1993;Morabito et al, 1998 (Thiel et al, 1996), adesão (Cronstein et al, 1990), produção dos radicais de oxigênio (Cronstein et al, 1985), degranulação (Richter, 1992) e produção de TNF-α (Thiel & Chouker, 1995 Tregs, e conseqüentemente, ocasionar a geração de células T ativadas refratárias à supressão mediada pela adenosina (Bansard et al, 2009). …”
Section: 43-células Tregs Na Arunclassified
“…Dados na literatura sugerem que a eficácia terapêutica observada com a utilização do MTX foi decorrente de sua capacidade em manter os níveis extracelulares de adenosina elevados (Cronstein et al, 2005;Montesinos et al, 2007;Morabito et al, 1998). No presente estudo, nós demonstramos um mecanismo de refratariedade de pacientes com AR ao tratamento com MTX baseado no número de células Tregs circulantes e na contribuição deste subtipo leucocitário para a geração de adenosina extracelular pelas ectonucleotidases presentes em sua superfície.…”
Section: -Discussãounclassified